2022
DOI: 10.3390/cancers14071640
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Immune Checkpoint Inhibitors in Advanced Urothelial Carcinoma

Abstract: Urothelial carcinoma is an aggressive cancer and development of metastases remains a challenge for clinicians. Immune checkpoint inhibitors (ICIs) are significantly improving the outcomes of patients with metastatic urothelial cancer (mUC). These agents were first used in monotherapy after failure of platinum-based chemotherapy, but different strategies explored the optimal use of ICIs in a first-line metastatic setting. The “maintenance” strategy consists of the introduction of ICIs in patients who experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Immune checkpoint inhibitors (ICIs) targeting program-cell death 1 or its ligand (anti-PD1/anti-PDL1) and cytotoxic T-lymphocyte associated protein 4 (anti-CTLA-4) have revolutionized the treatment paradigm for multiple cancers and have brought unprecedented deep and durable treatment efficacy to patients with metastatic disease [ 1 , 2 , 3 , 4 , 5 ]. Kidney cancer is one of the leading examples demonstrating how immune checkpoint inhibitors enable sustained long-term overall survival in metastatic disease: after a minimal 5-year follow-up of the CheckMate 214 trial [ 6 ], almost 50% of the ipilimumab/nivolumab treated metastatic clear cell renal cell carcinoma (mccRCC) patients were still alive, with a median overall survival of 56 months, compared to that of 38 months in the sunitinib arm among the intention-to-treatment population.…”
Section: Introductionmentioning
confidence: 99%
“…Immune checkpoint inhibitors (ICIs) targeting program-cell death 1 or its ligand (anti-PD1/anti-PDL1) and cytotoxic T-lymphocyte associated protein 4 (anti-CTLA-4) have revolutionized the treatment paradigm for multiple cancers and have brought unprecedented deep and durable treatment efficacy to patients with metastatic disease [ 1 , 2 , 3 , 4 , 5 ]. Kidney cancer is one of the leading examples demonstrating how immune checkpoint inhibitors enable sustained long-term overall survival in metastatic disease: after a minimal 5-year follow-up of the CheckMate 214 trial [ 6 ], almost 50% of the ipilimumab/nivolumab treated metastatic clear cell renal cell carcinoma (mccRCC) patients were still alive, with a median overall survival of 56 months, compared to that of 38 months in the sunitinib arm among the intention-to-treatment population.…”
Section: Introductionmentioning
confidence: 99%
“…The development of checkpoint inhibitors, including monoclonal antibodies against cytotoxic T-lymphocyte-associated protein 4, programmed cell death protein-1 (PD-1), and programmed death-ligand 1 (PD-L1), has revolutionized the treatment of a wide range of cancers. 1 , 2 Immune checkpoint inhibitors, including PD-(L)1 inhibitors, either as monotherapy or in combination with other anticancer therapies, have shown high levels of efficacy and become standard of care for a number of solid tumor types, including melanoma, 3 non-small-cell lung cancer (NSCLC), 4 urothelial carcinoma, 5 and renal cell carcinoma (RCC). 6 …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, as a result of an improved understanding of cancer immunobiology, systemic immunotherapies targeting immune checkpoint inhibitors (ICIs) have been explored and clinically applied for the treatment of urothelial carcinoma. 11 According to the results of several current clinical trials, PD-L1 expression is a biomarker that can indicate which patients will benefit the most from PD-1/PD-L1 −targeted therapies. 12,13 Several studies have demonstrated that PD-L1 expression can be evaluated in resection specimens and tissue microarray of UTUC, and have suggested that PD-L1 expression is associated with adverse pathological features and is an independent predictor of worse cancer-specific and overall survival.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, as a result of an improved understanding of cancer immunobiology, systemic immunotherapies targeting immune checkpoint inhibitors (ICIs) have been explored and clinically applied for the treatment of urothelial carcinoma 11 . According to the results of several current clinical trials, PD‐L1 expression is a biomarker that can indicate which patients will benefit the most from PD‐1/PD‐L1−targeted therapies 12,13 .…”
Section: Introductionmentioning
confidence: 99%